KICHIK MAKTAB YOSHIDAGI BOLALARNI MAKTABGA TAYYORLASHNING PSIXOLOGIK XUSUSIYATLARI - Mominova, X.E. (SCIENCE and SOCIETY, 2024)
It is known that our nation is rightfully proud of its great past, the incomparable contributions of our ancestors to world civilization, science, and culture. It is also known that when they were born and developed from early childhood, that is, there were no preschool educational institutions and psychologists in those days. At this point, "Do preschools and preschools need a practicing psychologist?" - the question may be raised. We can find the answer to such questions in the differences between the conditions of children’s development in the preschool period in the past and today. This article deals with such issues.